PENGARUH KUALITAS PRODUK, CITRA MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO GETUK ECO MAGELANG - Hallein Ridho Panggayuh; Ari Pradhanawati (Universitas Diponegoro, 2017)
rapidly is the food industry currently the culinary business in indonesia has rapidly increased. Inaddition, indonesia has a variety of food and traditional cuisine that must be developed and preserved.Getuk Eco as one of the food gifts manufacturer in Magelang City, is a trusted brand, but more numbersof food gifts producers in the City of Magelang causing Getuk Eco decreased their sales in 2014.The purpose of this research is to determine the effect of product quality, brand image andword of mouth towards purchasing decisions on Getuk Eco store Magelang. The type of research isexplanatory research. The population in this research is the consument of a Getuk Eco store with thenumber of samples taken was 100 respondents. Sampling using non probability sampling technique.Measurement scale using Likert scale. The analytical method used is the correlation test, determination,simple linear regression, multiple linear regression, t-test and F-test using SPSS program version 18.Based on the results of the research, revealed that the partially, product quality, brand imageand word of mouth has positive effect on the purchasing decision which is indicated by result of thevalue of t test bigger than t table. Significantly, variable product quality, brand image and word ofmouth has positive effect towards purchasing decision indicated by value of F test larger than F table.And the advice that can be given is product quality improvement, especially on packaging ofGetuk Eco’s product and aesthetics improvements. Besides, Getuk Eco also need to improve thecompany’s image as the best food gifts producer in Magelang City to support the consumer confidence.